Информационные модели наблюдаемых процессов для мониторинга компьютерных сетей - Саенко, В. И.; Гриценко, А. И. (НТУ "ХПИ", 2014)
Рассматриваются вопросы теории, методологии и практики мониторинга компьютерных сетей. Акцент сделан на описании характеристик наблюдаемых процессов, обобщаемых в виде информационных моделей. В основе работы лежит идея априорной определенности наблюдаемых процессов, для которых можно сформировать значения некоторых характеристик практически без проведения измерений. В рамках технологии WMI рассмотрен пример оценивания разработанных информационных моделей. Табл.: 3. Из.: 4. Библиогр.: 12 назв.

Two information models of controlled computer network processes are set forth. The models are to be used in tasks of controlled processes approximation for decreasing network monitoring data overhead. The main purpose is to describe controlled processes mathematically in order to have possibility to choose more precise approximation models for them. Therefore parameters of the models consist of numerical and analytical descriptions of the controlled processes. Special evaluating rules have been outlined for them. The practical part of the work describes the models evaluating example in the context of WMI. Despite using WMI concepts the models can be evaluated in the context of other network monitoring technologies, such as SNMP, JMX etc.
Information models of controlled processes for the computer network monitoring
Keywords: компьютерные сети; аппроксимация; аппроксимирующая модель; случайные процессы; информационные описания; networ; monitorin; WMI; CIM; approximation; stochastic process; information model